Generation of ultrahigh fields by microbubble implosion (Physical Sciences and Technology, 2019)
Breaking the 100-MeV barrier for proton acceleration will help elucidate fundamental physics and advancepractical applications from inertial confinement fusion to tumor therapy. A novel concept of “microbubbleimplosion (MBI)” is proposed. In the MBI concept, bubble implosion combines micro-bubbles and ultraintenselaser pulses of 1020 – 1022 Wcm-2 to generate ultrahigh fields and relativistic protons. The bubblewall protons are subject to volumetric acceleration toward the center due to the spherically symmetricelectrostatic force generated by hot electrons filling the bubble. Such an implosion can generate an ultrahighdensity proton core of nanometer size on the collapse, which results in an ultrahigh electrostatic field toemit energetic protons in the relativistic regime. Laser intensity scaling is investigated for acceleratedproton energy and attainable electrostatic field using MBI. Three-dimensional particle-in-cell andmolecular dynamics simulations are conducted in a complementary manner. As a result, underlying physicsof MBI are revealed such as bubble-pulsation and ultrahigh energy densities, which are higher by orders ofmagnitude than, for example, those expected in a fusion-igniting core of inertially confined plasma. MBIhas potential as a plasma-optical device, which optimally amplifies an applied laser intensity by a factor oftwo orders of magnitude; thus, MBI is proposed to be a novel approach to the Schwinger limit.